2001
DOI: 10.1021/ac010413y
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Electrochromatography for Separation of Peptides Driven with Electrophoretic Mobility on Monolithic Column

Abstract: A mode of capillary electrochromatography for separation of ionic compounds driven by electrophoretic mobility on a neutrally hydrophobic monolithic column was developed. The monolithic column was prepared from the in situ copolymerization of lauryl methacrylate and ethylene dimethacrylate to form a C 12 hydrophobic stationary phase. It was found that EOF in this hydrophobic monolithic column was very poor, even the pH value of mobile phase at 8.0. The peptides at acidic buffer were separated on the basis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 35 publications
2
78
0
Order By: Relevance
“…[21] and Wu et al [27] have achieved separations of peptides on the uncharged monolithic columns with poly (styrene-codivinylbenzene) and poly (lauryl methacrylate-co-ethylene dimethacrylate) rods. It was observed that peptides were separated on the basis of their difference in electrophoretic mobility and hydrophobic interaction with the stationary phase, and all of the basic peptides containing histidine and lysine showed good peak symmetry [27].…”
Section: Packed Column Capillary Electrochromatography Of Peptides Anmentioning
confidence: 99%
See 2 more Smart Citations
“…[21] and Wu et al [27] have achieved separations of peptides on the uncharged monolithic columns with poly (styrene-codivinylbenzene) and poly (lauryl methacrylate-co-ethylene dimethacrylate) rods. It was observed that peptides were separated on the basis of their difference in electrophoretic mobility and hydrophobic interaction with the stationary phase, and all of the basic peptides containing histidine and lysine showed good peak symmetry [27].…”
Section: Packed Column Capillary Electrochromatography Of Peptides Anmentioning
confidence: 99%
“…It was observed that peptides were separated on the basis of their difference in electrophoretic mobility and hydrophobic interaction with the stationary phase, and all of the basic peptides containing histidine and lysine showed good peak symmetry [27].…”
Section: Packed Column Capillary Electrochromatography Of Peptides Anmentioning
confidence: 99%
See 1 more Smart Citation
“…(9)], can be defined by analogy to the capacity factor, kЈ, in HPLC, as cec ϭ ͑t cec Ϫ t eo ͒ t eo (9) where t cec is the apparent migration time of the peptide and t eo is the migration time of the EOF marker. Alternative definitions have been proposed, [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] e.g., the apparent migration time of the peptide can also be related to the applied voltage E (in kV/m) and capillary length, or in the case of pressure-assisted electrochromatographic separations, 28 according to…”
Section: Introductionmentioning
confidence: 99%
“…The second group of CEC columns are continuous beds, also called monoliths [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Compare with packed capillaries, they are much easier to prepare.…”
Section: Types Of Cec Columnsmentioning
confidence: 99%